Effects of the non-native Arapaima gigas on native fish species in Amazonian oxbow lakes (Bolivia). - Danny Rejas; Monika Winder; Reinaldo Cholima; Thierry Oberdorff (PLoS ONE)
The introduction of non-native fish species into new environments has raised global concerns due to potential ecological impacts on recipient ecosystems. A previous study focusing on the introduced fish species Arapaima gigas in Bolivian Amazon waters showed that its isotopic niche significantly overlapped with most co-occurring native fish species, suggesting potential competition. To evaluate this hypothesis, we extended here the investigation by comparing the trophic position and isotopic niche width of eleven abundant native fish species inhabiting both colonized and non-colonized floodplain lakes. We found lower trophic positions in colonized versus non-colonized lakes only for native piscivores, mostly driven by a shift towards increased dietary proportion of detritivorous fishes. Conversely, results showed that the isotopic niche width of most fish species analyzed (i.e. 10 over 11 species) did not significantly decrease in colonized compared to non-colonized lakes. Our overall results suggest potentially low competitive interactions between A. gigas and native fishes, with the notable exception of piscivorous species. We attribute our findings to the high abundance of available resources in Amazon oxbow lakes.